Usability of a Web-Based School Experience System: Opinions of it teachers and teacher candidates - Genç, Zülfü (IADIS, 2015)
With advances in information and communication technologies, the classical nature of educational institutions has changed. One innovative effort within teacher training is the Web-Based School Experience System (WBSES) developed by the researcher. In this study, the usability of an existing WBSES is evaluated from both teachers' (n = 13) and students' (n = 96) perspectives. A non-experimental survey method was applied to collect participant opinions. A usability questionnaire was designed, and analysis yielded five significant factors for the system: usefulness, helpfulness, visual effectiveness, customizability, and smoothness. To obtain more in-depth information, participants were asked to delineate their responses to five open-ended questions. Generally, students and teachers liked the tool in terms of its usability, but they also provided recommendations for design issues.
International Conference on e-Learning 2015, E-LEARNING 2015 -- 21 July 2015 through 24 July 2015 -- Las Palmas de Gran Canaria -- 119136
Keywords: School experience; Teacher training; Teaching practice; Usability; Web-based learning environments